2016
DOI: 10.1016/j.bbadis.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein reverts L-valine-induced persistent sodium current up-modulation in primary cortical neurons

Abstract: L-valine is a branched-chain amino acid (BCAA) largely used as dietary integrator by athletes and involved in some inherited rare diseases such as maple syrup urine disease. This pathology is caused by an altered BCAA metabolism with the accumulation of toxic keto acids in tissues and body fluids with consequent severe neurological symptoms. In animal models of BCAA accumulation, increased oxidative stress levels and lipid peroxidation have been reported. The aim of this study was to analyze both whether high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
2
10
0
Order By: Relevance
“…Our results, obtained with embelin in cells in culture, are similar to those of baicalein, known to be an excellent antioxidant compound [18,28,29]. We also evaluated the capability of embelin microglia [32] to be cytotoxic for the cells or modulate proliferation by MTT assay and proliferation curves.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our results, obtained with embelin in cells in culture, are similar to those of baicalein, known to be an excellent antioxidant compound [18,28,29]. We also evaluated the capability of embelin microglia [32] to be cytotoxic for the cells or modulate proliferation by MTT assay and proliferation curves.…”
Section: Discussionsupporting
confidence: 71%
“…Since embelin biological antioxidant action needs a longer time with respect to other small molecules scavengers analyzed by our group [18,28], we suspected that the long tail of embelin could slow molecular mobility in the biological environment and be responsible for this delay. Taking advantage of the X-ray crystal structure of embelin [8], we built a model to mimic the cell membrane insertion of this scavenger.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…LaNoue and colleagues [ 246 ] found that approximately 30% of de novo glutamate synthesis came from transamination of BCAAs in the retina, and the ubiquity of the branched-chain aminotransferase in the CNS suggests that BCAA transamination is a significant contributor to de novo glutamate synthesis in the rest of the CNS as well [ 247 ]. High concentrations of BCAAs, such as those found in patients with maple syrup urine disease, were found to be neurotoxic due to increased excitotoxicity and oxidative stress [ 248 , 249 , 250 ].…”
Section: Amino Acidsmentioning
confidence: 99%
“…We also studied the effect of baicalein, a flavonoid from the roots of Scutellaria baicalensis, on THP-1 cell migration. Baicalein is a strong antioxidant also at very low concentrations in THP-1 monocytes, reported to be able to modulate also NO production (Seo et al, 2011;Lombardo et al, 2013;Caioli et al, 2016). Baicalein was able to inhibit significantly the cell migration induced by MCP-1, as well as DPI (Figures 7B,C).…”
Section: Role Of Reactive Oxygen and Nitrogen Species In The Migration Induced By Monocyte Chemoattractant Protein-1 In Thp-1 Monocytesmentioning
confidence: 87%